Search for top and bottom squarks from gluino pair production in final states with missing transverse energy and at least three b-jets with the ATLAS detector - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (The European physical journal. C, Particles and fields, 2012)
This letter reports the results of a search for top and bottom squarks from gluino pair production in 4.7 fb−1 of pp collisions at s√=7 TeVs=7 using the ATLAS detector at the LHC. The search is performed in events with large missing transverse momentum and at least three jets identified as originating from a b-quark. Exclusion limits are presented for a variety of gluino-mediated models with gluino masses up to 1 TeV excluded.
The ATLAS Collaboration: G. Aad, C.F. Anders, G. Anders, V. Andrei, Y. Davyora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.-E. Kluge, A. Kugel, V.S. Lang, V. Lendermann, F. Lepold, R. Maenner, K. Meier, F. Mueller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und 2845 weitere]
Gesehen am 29.11.2018